The Multimodal Issue - MacFarlane, Samantha (KULA)

(untitled) (University of Victoria Libraries, 2025)
Introduction to the multimodal scholarship issue of KULA: Knowledge Creation, Dissemination, and Preservation Studies. The issue brings together two short films, a research comic, an audio essay, a video essay, and an exhibition article. The six works in the issue come from a variety of disciplines and fields of research including visual anthropology, science and technology studies, socio-gerontechnology, literary studies, library science, audiovisual anthropology, and games studies. Together, they exemplify the exciting range of possibilities for scholarship in different mediums and modalities.